Assessment of school Learning Continuity Plan (LCP) implementation: Basis for policy formulation - Peregrino, Lilia P.; Javillonar, Mark G.; Caballes, Dennis G.; Necio, Chona R.; Ramirez, Amor B. (Goodwood Publishing, 2022)
Purpose: This study aimed at understanding how the Learning Continuity Plan was implemented in the schools in the Province of Palawan, Philippines Research methodology: It employed Quantitative and Qualitative Research Methods utilizing an interview questionnaire to gather needed data from twenty public schools in the province. Results: The schools’ LCP is still on the initial implementation as there are areas of concern that are yet to be fully accomplished. Problems involving funding, stakeholders’ collaboration, and institutional policy compliance are detrimental to smooth LCP implementation. Comparably, schools were able to implement collaboration, planning and review, strong communication, and transparency achieving the goals of education amidst problems. It was proven that schools could be resilient in times of a crisis as they could continue education amidst the challenges. Limitations: Since this study was conducted in the first year of LCP implementation amidst the coronavirus pandemic, the results may only be true to the said time and conditions. Contribution: This study could be a basis for developing policies for effective LCP implementation